Free Thyroxine Distinguishes Subclinical Hypothyroidism From Other Aging-Related Changes in Those With Isolated Elevated Thyrotropin - Abbey, Enoch J.; McGready, John; Sokoll, Lori J.; Simonsick, Eleanor M.; Mammen, Jennifer S. R. (Frontiers in Endocrinology, 2022)
Background Although a finding of isolated elevated thyrotropin (TSH) often leads to treatment with thyroid hormone, it is not specific to a diagnosis of subclinical hypothyroidism, particularly in older adults. We have previously used longitudinal assessment of TSH and free thyroxine (FT4) to distinguish primary and secondary changes in the hypothalamic-pituitary-thyroid (HPT) axis, an approach which is impractical for clinical diagnosis. Objective Identify contemporaneous clinical tests and criteria that predict the longitudinally-derived HPT axis phenotype in those with isolated elevated TSH. Methods Using data from Baltimore Longitudinal Study of Aging, participants with over three years of follow up not on thyroid hormone replacement, with a TSH above the reference range and an in-range FT4 at the current visit, and at least 1% per year increase in TSH (mean 6.9% annual increase; n=72), we examined correlations between various clinical factors and the change in FT4 across the phenotypic range from emerging hypothyroidism, with falling FT4, to adaptive stress-response, with rising FT4. Results Current FT4 level, but not TSH, Free T3, anti-TPO antibody status, age or sex, was significantly associated with phenotype, determined by the annual rate of change in FT4 in those with elevated and rising TSH, both as a continuous variable (β=0.07 per ng/dL increase in FT4; p<0.001) and in quartiles (p<0.001). We estimated a threshold for FT4 of less than 0.89 ng/dL (11.45 pmol/L; the 24th percentile of the reference range), as predictive of a phenotype in the first quartile, consistent with subclinical hypothyroidism, while a FT3:FT4 ratio below 2.77 predicted a phenotype in the fourth quartile, more consistent with adaptive stress-response. Conclusions In those with isolated elevated TSH, a FT4 in the lowest quartile of the reference range differentiates those with developing hypothyroidism from other HPT-axis aging changes.